2011
DOI: 10.1038/ejhg.2011.170
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide homozygosity and multiple sclerosis in Orkney and Shetland Islanders

Abstract: There is strong evidence for both genetic and environmental risk factors comprising the aetiology of multiple sclerosis (MS). While much progress has been made in recent years in identifying common genetic variants using genome-wide association studies, alternative approaches have remained relatively neglected. The prevalence of MS in Orkney and Shetland is among the highest in the world. Previous studies have suggested that a higher degree of parental relatedness in these isolated communities may contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 35 publications
3
16
1
Order By: Relevance
“…However, it could be a true difference between the populations. McWhirther et al 19 found a mean pair-wise kinship (pi-hat) of 0.004 in their Orkney and Shetland sample whereas it was 0.01697 in our population sample. Furthermore, the observed number of homozygotes was also greater in our sample indicating that the population of the Faroe Islands are more closely related than those of the Orkney and Shetland Islands.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…However, it could be a true difference between the populations. McWhirther et al 19 found a mean pair-wise kinship (pi-hat) of 0.004 in their Orkney and Shetland sample whereas it was 0.01697 in our population sample. Furthermore, the observed number of homozygotes was also greater in our sample indicating that the population of the Faroe Islands are more closely related than those of the Orkney and Shetland Islands.…”
Section: Discussioncontrasting
confidence: 70%
“…It is an estimate of the size of an individual's recent and ancient ancestral gene pool. 19 2) Number of ROHs at the following lengths ≥1 mega base pairs (Mb), ≥1.5 Mb, ≥2.5 Mb and ≥5 Mb. Short ROHs are found in all populations, whereas long ROHs are almost only seen in more isolated populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases of doubt, a senior neurologist made the final decision. Some patients (n=81) taking part in a parallel genetics study19 were examined by the research fellow. We recorded the subtype of MS (relapse–remitting, secondary progressive and primary progressive), and disability status was scored using a modified Expanded Disability Status Scale (EDSS)20 (mild 0–2.5, mild to moderate 3–5.5, moderate to severe 6–7.5 and severe 8–9.5) estimated from the patient records.…”
Section: Methodsmentioning
confidence: 99%
“…Geographic isolation of populations may lead to a considerable loss of diversity, an increase in inbreeding and vulnerability to stochastic events [ 6 ]. For instance, human populations with a history of prolonged isolation on the Orkney or Dalmatian Islands or in Sardinia have longer ROH than continental populations, which indicates an elevated relatedness [ 7 , 8 ]. A high frequency of ROH can have detrimental effects on biological fitness and reproductive success because ROH are often enriched in deleterious mutations [ 9 ].…”
Section: Introductionmentioning
confidence: 99%